2021
DOI: 10.1371/journal.pone.0248809
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for the classification of fractures around the knee in adults according to the 2018 AO/OTA classification system

Abstract: Background Fractures around the knee joint are inherently complex in terms of treatment; complication rates are high, and they are difficult to diagnose on a plain radiograph. An automated way of classifying radiographic images could improve diagnostic accuracy and would enable production of uniformly classified records of fractures to be used in researching treatment strategies for different fracture types. Recently deep learning, a form of artificial intelligence (AI), has shown promising results for interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…This study is part of a model developed and validated as a diagnostic tool using our database containing radiographic examinations collected from our radiology department at Danderyd University Hospital. Recently, we have also published our results by Lind, et al [ 18 ] based on this diagnostic method as it was able to use artificial intelligence to identify and classify fractures. The details of the source of data, extracting methods, neural network setup, outcome measures, and statistical analysis were identical with the previously published article [ 18 ].…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…This study is part of a model developed and validated as a diagnostic tool using our database containing radiographic examinations collected from our radiology department at Danderyd University Hospital. Recently, we have also published our results by Lind, et al [ 18 ] based on this diagnostic method as it was able to use artificial intelligence to identify and classify fractures. The details of the source of data, extracting methods, neural network setup, outcome measures, and statistical analysis were identical with the previously published article [ 18 ].…”
Section: Methodsmentioning
confidence: 90%
“…Recently, we have also published our results by Lind, et al [ 18 ] based on this diagnostic method as it was able to use artificial intelligence to identify and classify fractures. The details of the source of data, extracting methods, neural network setup, outcome measures, and statistical analysis were identical with the previously published article [ 18 ].…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, Karnuta et al 18 used AI to differentiate between knee arthroplasty implants from different manufacturers with near-perfect accuracy. Lind et al 21 also showed that AI could identify fractures around the knee in adults according to the 2018 AO/OTA classification system with performance similar to that of senior orthopaedic surgeons. In this study, we used AI to perform 3D reconstruction of CT data of lower limbs and compared its performance with the operator-based approach.…”
Section: Discussionmentioning
confidence: 96%
“…[18][19][20] For example, Karnuta et al 18 used AI to identify arthroplasty implants from radiographs of the knee. Lind et al 21 also utilised AI to identify and classify fractures of the knee. In this study, we explored the use of AI to perform 3D reconstruction of CT data of lower limbs.…”
mentioning
confidence: 99%